Risk factors for chronic non-communicable diseases and the CARMEN Initiative: a population-based study in the South of Brazil Fatores de risco para doenças crônicas não-transmissíveis e a Iniciativa CARMEN: estudo de base populacional no sul do Brasil - Marcelo Fernandes Capilheira; Iná S. Santos; Mario Renato Azevedo Jr; Felipe Fossati Reichert (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The CARMEN Initiative is a strategy of the Pan American Health Organization and the World Health Organization that proposes population-based interventions to reduce risk factors for chronic non-communicable diseases (CNCD) by approaching them simultaneously. The present study aims to provide a baseline for further interventions by the CARMEN Initiative based on a cross-sectional population-based study of 3,100 adults (>20 years old) in Pelotas, a city in the South of Brazil. Prevalence of smoking, physical inactivity, diabetes mellitus, hypertension, and excess weight were studied and presented separately and aggregated in various combinations. The most frequent risk factor was physical inactivity (73.2%), followed by excess weight (48.1%). Women were less active and thinner than men. More than half of the sample showed two or three risk factors (53.4%). The combination of physical inactivity and excess weight was observed in 34.7% of the sample, while 10.8% presented physical inactivity, excess weight, and hypertension concurrently. The accumulation of risk factors for CNCD is frequent in the study population and the identification of the most common combinations is essential for planning future interventions. A Iniciativa CARMEN é uma estratégia da Organização Pan-Americana da Saúde e da Organização Mundial da Saúde de combate às doenças crônicas não-transmissíveis, que prevê intervenções populacionais para a redução simultânea de seus fatores de risco. Pretende-se fornecer uma linha de base para intervenções da Iniciativa CARMEN valendo-se de um estudo de base populacional com 3.100 adultos (> 20 anos), moradores de Pelotas, Rio Grande do Sul. Os fatores estudados foram: tabagismo, sedentarismo, diabetes mellitus, hipertensão arterial sistêmica e excesso de peso, sendo descritos acumulados, isoladamente e em combinações. O sedentarismo foi o fator de risco mais prevalente (73,2%), seguido do excesso de peso (48,1%). As mulheres foram mais sedentárias e mais magras que os homens. Mais da metade da população apresenta dois ou três fatores de risco (53,4%). A combinação de sedentarismo e excesso de peso ocorreu em 34,7% da amostra; e sedentarismo, excesso de peso e hipertensão, em 10,8%. O acúmulo de fatores de risco para doenças crônicas não-transmissíveis é freqüente na população estudada e a identificação das suas combinações mais prevalentes é de grande relevância para o planejamento de intervenções futuras.